2007
DOI: 10.1074/jbc.m611397200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible Factor-1α, a Key Factor in the Keratinocyte Response to UVB Exposure

Abstract: Hypoxia-inducible factor-1 (HIF-1) is a major transcription factor sensitive to oxygen levels, which responds to stress factors under both hypoxic and nonhypoxic conditions. UV irradiation being a common stressor of skin, we looked at the effect of UVB on HIF-1␣ expression in keratinocytes. We found that UVB induces a biphasic HIF-1␣ variation through reactive oxygen species (ROS) generation. Whereas rapid production of cytoplasmic ROS down-regulates HIF-1␣ expression, delayed mitochondrial ROS generation resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
96
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 53 publications
13
96
2
Order By: Relevance
“…UVR mediated changes to phospholipids is therefore thought to occur as a result of photo-oxidation reactions 80 . Recent studies by photobiologists indicate that UVB generates ROS through a series of sequential steps involving: EGFR activation, ROS generation by cytosolic NADPH oxidase, ras/ERK & p38MAPK activation, p53 activation, and finally apoptotic signaling leading to mitochondrial ROS generation [81][82][83][84][85][86][87][88] . Thus, UVBmediated ROS are likely involved in the generation of ox-GPCs.…”
Section: Mechanisms By Which Uvb Generates Ox-gpcsmentioning
confidence: 99%
“…UVR mediated changes to phospholipids is therefore thought to occur as a result of photo-oxidation reactions 80 . Recent studies by photobiologists indicate that UVB generates ROS through a series of sequential steps involving: EGFR activation, ROS generation by cytosolic NADPH oxidase, ras/ERK & p38MAPK activation, p53 activation, and finally apoptotic signaling leading to mitochondrial ROS generation [81][82][83][84][85][86][87][88] . Thus, UVBmediated ROS are likely involved in the generation of ox-GPCs.…”
Section: Mechanisms By Which Uvb Generates Ox-gpcsmentioning
confidence: 99%
“…High efficiency of lentiviral vector-mediated gene transfer in normal and XPC keratinocytes As previously shown, lentiviral vectors provide high efficiency and sustained transgene expression in normal human keratinocytes. [22][23][24] In this study, the same type of lentivectors was used for the transduction of XPC keratinocytes to overexpress either the marker gene EGFP (TPEW) or the 'therapeutic' gene catalase (TPCATW) (Figure 2a). The percentage of EGFPpositive cells assessed by cytofluometry 5 days post-transduction reached 85-95% both in normal and XPC cells (Figure 2b).…”
Section: Xpc Molecular Analysesmentioning
confidence: 99%
“…[16][17][18][19][20] Several studies have shown that keratinocyte exposure to UVB irradiation generates ROS in excessive quantities that quickly overwhelm various antioxidant defense systems including non-enzymatic (a-tocopherol and vitamin C) and enzymatic antioxidants (catalase and superoxide dismutase). [21][22][23][24] UVB-induced ROS production leads to cytotoxicity through proteins, lipids and DNA oxidation both in vitro and in vivo. 21,[25][26][27] Unlike lipids and proteins, damaged DNA molecules cannot be replaced and need to be repaired.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a key role has been demonstrated for epidermal growth factor receptor (EGFR), a prominent receptor tyrosine kinase in keratinocytes (39), in relaying UVB-induced responses (40). It is also important to distinguish between immediate and delayed effects (41). This versatility in responses and the multitude of pathways potentially activated could account for the dynamic temporal patterns previously observed in hyaluronan secretion and HAS expression.…”
mentioning
confidence: 99%